2002
DOI: 10.1007/s00122-002-0911-7
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage map of Guinea yam (Dioscorea rotundata Poir.) based on AFLP markers

Abstract: A genetic linkage map of the tetraploid white yam ( Dioscorea rotundata Poir.) was constructed based on 341 co-dominantly scored amplified fragment length polymorphism (AFLP) markers segregating in an intraspecific F(1) cross. The F(1) mapping population was produced by crossing a landrace cultivar TDr 93-1 as female parent to a breeding line TDr 87/00211 as the male parent. The marker segregation data were split into maternal and paternal data sets, and separate genetic linkage maps were constructed since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 36 publications
(41 reference statements)
3
35
0
Order By: Relevance
“…Also, while the overall distribution of the AFLP markers appeared satisfactory some E/M markers clustered in specific chromosomal regions. Clustering of E/M markers was also observed in D. rotundata (Mignouna et al 2002a). If the rather low level of heterozygosity observed in D. rotundata (Zoundjihékpon et al 1994) also applies to D. alata, that may explain the relatively low level of polymorphic markers detected by PstI.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Also, while the overall distribution of the AFLP markers appeared satisfactory some E/M markers clustered in specific chromosomal regions. Clustering of E/M markers was also observed in D. rotundata (Mignouna et al 2002a). If the rather low level of heterozygosity observed in D. rotundata (Zoundjihékpon et al 1994) also applies to D. alata, that may explain the relatively low level of polymorphic markers detected by PstI.…”
Section: Discussionmentioning
confidence: 64%
“…Amplified fragment length polymorphism (AFLP) markers are an excellent source of polymorphisms in eucaryotic genomes and have been shown to be well-suited for genotyping and map construction in several plant species, including yam (Mackill et al 1996;Mignouna et al 1998;Mignouna and Asiedu 1999;Terauchi and Kahl 1999;Mignouna et al 2001b). Terauchi and Kahl (1999) produced a genetic linkage map of Dioscorea tokoro Makino, a diploid wild yam species classified in the botanical section Stenophora that is phylogenetically distant from the cultivated yams in the Section Enantiophyllum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genetic diversity and phylogenetic relationships in Dioscorea were determined with isozymes or DNA markers (Asemota et al, 1996;Dansi et al, 2000;Hamon and Touré, 1990;Mignouna et al, 1998Mignouna et al, , 2002aRamser et al, 1996Ramser et al, , 1997Terauchi et al, 1992;Zoundjihékpon et al, 1994). Today, AFLP maps of the water yam include 338 markers on 20 linkage groups (1055 cM) (Mignouna et al, 2002b), whereas there are 107 markers in 12 linkage groups (585 cM) for male and 13 linkage groups (700 cM) for female in the white yam (Mignouna et al, 2002c).…”
Section: Advances In Dna Mapping and Potential Of Marker-aided Breedingmentioning
confidence: 99%
“…Three QTL and one QTL, with effects on resistance to YMV, the most widespread and economically important viral disease affecting white yam, were identified on the maternal and paternal linkage maps, respectively (Mignouna et al, 2002c). Segregation ratios from early research indicated that a single dominant gene in a simplex condition governs the resistance in clone TDr 89/01444, while the resistance in clone TDr 93-2 is associated with the presence of a major recessive gene in duplex configuration (Mignouna et al, 2001b).…”
Section: Advances In Dna Mapping and Potential Of Marker-aided Breedingmentioning
confidence: 99%